Echocardiographic Predictors of Non Rheumatic Atrial Fibrillation - Methab Athab Al Missary, Ahmed (Diyala Journal of Medicine, 2019)
Objective: to assess echocardiographic structural&functional changes in non rheumatic AF Patients And Methods: 200 Patients were divided into 3 groups: Group A: Patients with AF,Group B: Patients have one or more of risk factors (hypertension, IHD, DM, HF, old age) without AF,Group C: normal healthy individuals. A full medical history and complete physical examination and the following investigation were arranged: FBS, RBS, ECG, CXR and echocardiograph. Result :The study show there is a significance increase in LAD ,LVEDS ,LVEDD and decrease in fractional shortening in group A &B And group A greater than group B and both groups greater than group C. Conclusion: Subjects with increase LA size, LVEDS, LVEDD and decrease in fractional shortening were at a significance increase risk for development of AF. This study clarifies the role of cardiac structural& functional characteristics’ in relation to susceptibility to AF .so the best method for reducing the adverse complication of AF through prevention of development of AF.